Severe maternal–fetal pathological damage and inflammatory responses contribute to miscarriage caused by hepatitis E viral infection during pregnancy. (28th November 2022) - Xia, Yueping; Yang, Weimin; Li, Yi; Qian, Zhongyao; Chen, Shuangfeng; Zhang, Yike; Cong, Chao; Li, Tengyuan; Liu, Huichan; Chen, Dongxue; Zhao, Wanqiu; Zhong, Guo; et al.
Abstract: Background: Hepatitis E virus (HEV) infection causes serious adverse pregnancy outcomes during pregnancy. However, the maternal and fetal damage induced by HEV infection is rarely reported. Methods: A BALB/c pregnant mouse model was established to explore the maternal and fetal pathological damage and inflammatory responses caused by HEV infection. Results: Notably, miscarriages and stillbirths were observed in HEV‐infected pregnant mice. HEV infections were identified by qRT‐PCR, immunohistochemical analysis and immunofluorescence assay in the uterus, placenta, umbilical cords and livers and brains of fetuses. Serious inflammatory responses and pathological damage were triggered in the uterus and placenta of HEV‐infected pregnant mice. Vertical transmission of HEV resulted in severe pathological damage and inflammatory responses in the livers and brains of fetuses, as well as emerging apoptosis cells in the brains of fetuses. Most of the cytokines/chemokines in the sera were significantly increased in the HEV‐infected pregnant mice. Remarkably, cytokines/chemokines were significantly different between HEV‐infected pregnant and miscarriage mice; IL9, GM‐CSF and IL1α were the most important three cytokines/chemokines in determining the pregnancy outcomes. Conclusion: HEV infections cause serious maternal/fetal pathological damage, inflammatory responses and apoptosis, which may be responsible for adverse pregnancy outcomes.